Publisitas Politik Aceng Aziz Muslim Menuju Pemilihan Umum 2024 di Facebook - Muldani, Trisno; Swarnawati, Aminah; Muksin, Nani Nurani; Harmonis, Harmonis (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
General elections (elections) are one of the routine agendas that characterize a democratic country like Indonesia. Ahead of the 2024 elections, political actors and their parties are competing to introduce themselves in advance, including through political publicity activities. Likewise, Aceng Aziz Muslim plans to run for the Tasikmalaya Regency Legislative Council in Election District 7 (Dapil 7) and the media chosen for these activities is Facebook. This study aims to determine the political publicity of Aceng Aziz Muslim on Facebook, as well as what are the supporting and inhibiting factors. The research results show that Aceng Aziz Muslim's political publicity in Indonesia has reached a significant level of attention throughout his career. He managed to build a strong social network in cyberspace, allowing him to gain wide access to various audiences on Facebook. His ability to identify issues relevant to the community and create creative content has also sustained public interest and support over the long term. The use of social media platform analytics tools has also been beneficial in measuring the impact of his publications. However, Aceng Aziz Muslim also faced a number of challenges in his efforts to build his political publicity on Facebook.